Uji Pengaruh Suhu Pengeringan pada Karakteristik Kimia dan Sensori Kaldu Bubuk Kepala Ikan Gabus (Channa striata) - Akhmad Sobri; Herpandi Herpandi; Susi Lestari (Jurnal FishtecH, 2017)
The purposes of this research was to investigate the proximate content, amino acid content and sensory snakehead fish (Channa striata) powder broth with the effect of drying temperature. The research was conducted on April 2016 to August 2016. The research method was used randomized block design (RBD). Drying temperature treatment used 50 oC, 60 oC and 70 oC. The parameters of this research was proximate analysis such as water content, ash content, protein content, lipid content, and carbohydrate content while for amino acid analysis only to find out the amount of essential amino acids and non-essential course and analytical sensory (appearance, flavor, texture, color and taste). Proximate content gave significant effect on protein content and there was no effect on water content, ash content, fat and carbohydrate content. Gave significant effect on sensory analysis (appearance, flavor, texture, color and taste). The concentration of protein content of the resulting broth powder ranges from 11.99% to 20.94%, there are eight types of essential amino acids and 7 types of non-essential amino acids while sensory analysis produced for sightings range from 3.72 to 4.52, flavor range between 3.8 to 4.32, textures range from 3.52 to 4.4, color range from 1.88 to 3.8 and taste range from 3.84 to 4.4.